Relevant factors contributing to risk of suicide among adolescents - Lingfei Cheng; Weijie Song; Yanli Zhao; Hongxin Zhang; Jian Wang; Jingyu Lin; Jingxu Chen (BMC Psychiatry)
Abstract Background Adolescent suicide is a major public health concern; therefore, this study evaluated the factors related to suicide risk in adolescents. Methods A questionnaire-based, cross-sectional survey was conducted in Beijing, China. Participants completed general information questionnaires developed for this study: the Patient Health Questionnaire-9; Generalized Anxiety Disorder 7-item; Revised Adverse Childhood Experience Questionnaire; Self-Hate Scale; Adolescent Non-Suicidal Self-Injury Assessment Questionnaire; and the Chinese version of the five-item MINI, suicide module. SPSS 22.0 software was used for the data statistics and Spearman’s correlation analysis, and the significance of the mediating effect was tested using the non-parametric percentile bootstrapping method with bias correction. Results Girls had a higher risk of suicide than boys (χ2 = 16.443). Adolescents with suicide risk compared to those without suicide risk were more likely to experience depression (z = 19.359, p < .001), anxiety (z = 19.958, p < .001), adverse childhood experiences (z = 17.866, p < .001), self-hate (z = 18.926, p < .001), and non-suicidal self-injury (z = 21.593, p < .001). In the mediation analysis, adverse childhood experiences directly affected suicide risk; the direct effect was 0.135, with 50.94% of the variance explained (p < .001). Adverse childhood experiences indirectly affected suicide risk through self-hate; the indirect effect was 0.130, with 49.06% of the variance explained (p < .001). Conclusions Sex, depression, anxiety, adverse childhood experiences, self-hate, and non-suicidal self-injury were associated with suicide risk in adolescents. Self-hate mediated the relationship between adverse childhood experiences and suicide risk. Suicide prevention efforts should focus on reducing the negative impact of these risk factors. This study provides important evidence-based support for adolescent suicide prevention and intervention strategies. Clinical trial number Not applicable.